Improvement of Facility Layout by Using Data Mining Algorithms and an Application - KOKOÇ, Melda; ERSÖZ, Süleyman; AKTEPE, Adnan; TÜRKER, Ahmet Kürşad (Prof. Dr. Ismail SARITAS, 2016)
The facility layout problems are always important in the production or service industry system. For many years, it has been a common research field in active research. It seen that various methods were used in literature review for improving facility layout. We used association analysis which is one of the techniques of data mining in this study. The primary aim of this study is to improving the emergency departments efficiency, increasing patient satisfaction and employee satisfaction, decreasing travelled distance in emergency department. In this study, data acquired from information system of an emergency service was examined by means of data mining techniques (association rules such as GRI and Apriori) and relations between departments were found out. Association rules were analyzed via data mining techniques applied and then departments having more flow density with each other were determined. In consideration of this information an alternative facility layout planning was planned in regard to analysis results of departments’ closeness situations, advices of emergency service doctor and observations made.